18. Technical and Interpretive Considerations in the Third Sonata for Violin and Piano, OP. 45 by Edvard Grieg - Ioniță Raluca Dobre (Sciendo, 2020)
Considered one of the founders of the Norwegian national music culture, Grieg sought to transpose into his music the grandeur of nature, the simplicity of people and their lives, the richness of fantasy and mythological stories. Edvard Grieg retains in his music essential elements of Norwegian folklore, which he uses in his own language. The third Sonata for violin and piano, op. 45 differs from the other two sonatas created previously, both by the dramatic character of the thematic material, as well as by the massive dimensions and the structure of the form that approaches the classical pattern. Starting with this Sonata, Grieg definitely crystallizes his style in the field of chamber music, revealing a mature language of dramatic essence, in which we find rich and inventive rhythmic and melodic structures, plastic harmonies and bold dissonances, picturesque timbre effects that capture the atmosphere and the specific Norwegian color.